(untitled) (The Agriculturists, 2017)
An experiment was conducted on in vitro regeneration and multiplication of Dendrobium bensoniae. Different concentrations of BA and IBA alone or combination of both hormones were used as treatment for regeneration. It was revealed that shoot regeneration from node was the best at 2.0 mg/l BA supplemented to MS medium. It gave better responses than all other concentrations and combinations of BA and BA+IBA, used in the present study. The highest number of shoots and leaves were found when 1.0 mg/l BA with 1.5 mg/l IBA was supplemented into MS medium. For rooting, 0.5 mg/l BA with 1.0 mg/l IBA was found to be the most effective. The well-rooted plantlets were successfully acclimatized under 70-80% humidity and planted in pots and transferred to the shade house for establishment. Around 85% of plantlets survived in the field. From the present result, it may be recommended that MS medium supplemented with 2.0 mg/l BA may be used for rapid shoot induction and regeneration of D. bensoniae. The Agriculturists 2016; 14(2) 24-31